Mapping common dolphin (Delphinus delphis) behaviour in the southern coast of Portugal - Araújo, Sara Miguel de Matos e (2023)
It is essential to know how common dolphins (Delphinus delphis) use their habitats so that conservation priorities can be defined, and the impacts of, for instance, anthropogenic activities can be mitigated. Study the behaviour of common dolphins can contribute not only to the protection of the population and ecosystem, but also to achieve several international and national goals regarding sustainable development. The common dolphin is one of the most widely distributed dolphin species and one of the most common cetaceans in Portuguese waters. The south coast of Portugal is a nursery and calving ground for common dolphins, but little is known about their behaviour patterns in this area. Therefore, this work aims to enhance the current knowledge on the habitat use of common dolphins by mapping and modelling their behaviour in the Algarve. The dataset used for the mapping consisted of sightings of common dolphins in the Algarve collected by AIMM – Marine Environment Research Association onboard a dedicated research boat between 2015 and 2020 following random trajectories. To model the occurrence of different behavioural states (i.e., travelling, socialising, foraging, and resting) in relation to the presence/absence of calves and several environmental variables (sea surface temperature, sea surface height above the geoid, bathymetry/distance to coast, slope, and substrate type), multinomial logistic regression models were created. The four behaviours analysed showed a similar overall distribution pattern, with some hotspots in offshore regions of the study area. Travelling was the most common behavioural state, while resting was rarely sighted. The selected model retains temperature and bathymetric slope as significant variables to describe dolphins’ behaviour. The modelling results suggest that as the temperature rises, resting behaviour is more likely to be observed compared to travelling. Furthermore, as slope increases, socialising behaviour is less likely to be observed compared to travelling. These results suggest that, in the current climate change scenario, the increase of water temperature in the study area could lead to an increase in the frequency of resting behaviour of common dolphins inhabiting the area, which could increase the vulnerability of the animals to predators and compromise other essential behaviours, such as foraging. However, more studies are needed to confirm this potential effect. Results also show that this species prefer flatter areas for socialising, which coincide with areas closer to the coast and that offer greater protection against predators. However, more coastal waters are also areas where human activities tend to concentrate. The disruption of social activities by anthropogenic stressors can lead to consequences on the population-level. Therefore, it is important for conservation measures to consider these areas, as they are used for essential behaviours. The implementation of scientific based conservation measures is urgent, considering that in the study area, the results show regular violations of the whale-watching norms by tour boats. Therefore, future studies should also consider, for instance, the effects of vessels on the behaviour of common dolphins in this area.